1990
DOI: 10.1172/jci114846
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous angiotensin concentrations in specific intrarenal fluid compartments of the rat.

Abstract: To examine angiotensin (ANG) concentrations in fluid compartments near known intrarenal ANG receptors, we measured ANG concentrations in glomerular filtrate (GF), star vessel plasma (SVP), and luminal fluid from the early, mid, and late proximal tubule (E, M, and L PT). Samples were collected from euvolemic Munich-Wistar rats by free-flow micropuncture; ANG concentrations were measured by RIA. In one group of rats, concentrations of total immunoreactive ANG (reflecting ANG II and lesser amounts of three fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
252
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(263 citation statements)
references
References 35 publications
8
252
0
3
Order By: Relevance
“…Medullary angiotensin II levels are higher than cortical levels (27). At the end of the proximal tubule, intratubular angiotensin II concentration has been measured in the 10 Ϫ9 -10 Ϫ8 M range (29,35). The angiotensin II concentration in the tubular fluid of other segments of the nephron remains unknown, but because angiotensin II levels in final urine have also been reported to be in the nanomolar range (27) and because intratubular angiotensin II is mainly produced in the proximal tubule, it is likely that luminal angiotensin II concentration in the MTALH is also much higher than the plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Medullary angiotensin II levels are higher than cortical levels (27). At the end of the proximal tubule, intratubular angiotensin II concentration has been measured in the 10 Ϫ9 -10 Ϫ8 M range (29,35). The angiotensin II concentration in the tubular fluid of other segments of the nephron remains unknown, but because angiotensin II levels in final urine have also been reported to be in the nanomolar range (27) and because intratubular angiotensin II is mainly produced in the proximal tubule, it is likely that luminal angiotensin II concentration in the MTALH is also much higher than the plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…While there is ample data to support that furosemide leads to increases in circulating levels of renin, data documenting how furosemide (and other diuretics) affects components of the intrarenal RAS is absent. This is particularly relevant with respect to intratubular and intrarenal levels of ANG II, which shows very substantial compartmentalization and have been reported to be up to 1,000 and 100 times plasma levels of ANG II, respectively (19,143). Conversely, data about the natriuresis in response to furosemide in the absence and presence of inhibitors of the RAS is limited and not consistent.…”
Section: Questions Pertaining To the Natriuretic Response To Furosemidementioning
confidence: 97%
“…The renal outer medulla is inaccessible to micropuncture, so that direct sampling of outer medullary DVR plasma directly downstream of juxtamedullary glomeruli cannot be performed. Seikaly and colleagues (142) found that ANG II concentrations in star vessel plasma sampled downstream of superficial glomeruli exceed circulating levels by as much as 1,000-fold. On this basis, it seems possible that DVR could be exposed to nanomolar ANG II in vivo.…”
Section: Role Of Dvr Endothelia In the Regulation Of Vasoactivitymentioning
confidence: 99%